Optimized Liquid-Liquid Extractive Rerefining of Spent Lubricants - Muhammad Ashraf Kamal; Syed Mumtaz Danish Naqvi; Fasihullah Khan (The Scientific World Journal)
Central composite design methodology has been employed to model the sludge yield data obtained during liquid-liquid extractive rerefining of spent lubricants using an alcohol (1-butanol) and a ketone (methyl ethyl ketone) as prospective solvents. The study has resulted in two reasonably accurate multivariate process models that relate the sludge yield (R2=0.9065 and 0.9072 for alcohol and ketone, resp.) to process variables (settling time t, operating temperature T, and oil to solvent ratio r). Construction of such models has allowed the maximization of the sludge yield (more than 8% and 3% in case of alcohol and ketone, resp.) so that the extraction of useable oil components from spent lubricants can economically be performed under extremely mild conditions (t = 16.7 h, T=10°C, and r=2) and fairly moderate conditions (t = 26.6 h, T=10°C, and r=5) established for the alcohol and ketone correspondingly. Based on these performance parameters alcohol appears to be superior over ketone for this extraction process. Additionally extractive treatment results in oil stocks with lesser quantity of environmentally hazardous polyaromatic hydrocarbons that are largely left in the separated sludge.